2017
DOI: 10.1596/978-1-4648-1056-5
|View full text |Cite
|
Sign up to set email alerts
|

Lessons Learned from World Bank Education Management Information System Operations: Portfolio Review, 1998-2014

Abstract: World Bank Studies are published to communicate the results of the Bank's work to the development community with the least possible delay. The manuscript of this paper therefore has not been prepared in accordance with the procedures appropriate to formally edited texts. This work is a product of the staff of The World Bank with external contributions. The findings, interpretations, and conclusions expressed in this work do not necessarily reflect the views of The World Bank, its Board of Executive Directors, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…Potential reasons included unrealistic EMIS goals, unclear definition and understanding of the EMIS, and over-reliance on central development of the EMIS (Abdul-Hamid, Saraogi and Mintz, 2017 [73]). The review calls for evaluating EMISs' potential according to the four core policy areas identified in the System Assessment and Benchmarking for Education Results (SABER) EMIS framework, namely enabling environment, system soundness, quality data, and utilisation for decision making (Abdul-Hamid, 2014 [74]; Porta and Arcia, 2011 [75]).…”
Section: The Education Monitoring System and The Importance Of The Ed...mentioning
confidence: 99%
“…Potential reasons included unrealistic EMIS goals, unclear definition and understanding of the EMIS, and over-reliance on central development of the EMIS (Abdul-Hamid, Saraogi and Mintz, 2017 [73]). The review calls for evaluating EMISs' potential according to the four core policy areas identified in the System Assessment and Benchmarking for Education Results (SABER) EMIS framework, namely enabling environment, system soundness, quality data, and utilisation for decision making (Abdul-Hamid, 2014 [74]; Porta and Arcia, 2011 [75]).…”
Section: The Education Monitoring System and The Importance Of The Ed...mentioning
confidence: 99%
“…The absence of clarity about the EMIS in some instances arose from the absence of a culture driven by data. (Abdul-Hamid et al, 2017).…”
Section: Challenges In Emis Implementationmentioning
confidence: 99%
“…Much time lags occurred in the publication and dissemination of information, thereby reducing the utility of data for decision making. Major causes for the failure were the inability of the government to understand the definition of EMIS, its objectives, and its usefulness in decision making (Abdul-Hamid et al, 2017).…”
Section: Challenges In Emis Implementationmentioning
confidence: 99%
See 1 more Smart Citation
“…The common goal of these efforts has been to improve education through better data for authorities and practitioners. A recent review (Abdul-Hamid et al, 2017) of these data systems as part of education sector development indicated that, together with obvious benefits, developing countries often suffered from misalignment of data handling activities, institutionalizing of these information systems, and lack of capacity to maintain data use reliable and trustworthy.…”
mentioning
confidence: 99%